THE COMPREHENSION OF REFLECTIVE PRACTICE AMONG EFL PROFESSIONAL TEACHERS IN INDONESIA: A CASE STUDY - Asep Dedeh Permana; Eri Kurniawan; Lulu Laela Amalia (STKIP Siliwangi, 2023)
In English Language Teaching, reflective practice is a significant pedagogical approach for teacher professional development. This study aims to find out the comprehension of six Professional EFL Teachers in West Java, Indonesia. The research addressed two research questions: (1) how the participants define reflective practice; and (2) how they practice their reflection. The researcher applied a case study using semi-structured interviews, observation and document analysis to collect the data, which then was analyzed thematically. The participants of this study were six professional English teachers who has passed the Teacher professional education program (PPG) and has been teaching more than 10 years. According to the findings, the participants view reflective practice as a method of evaluation and introspection which positively contribute to their professional development. The participants depend heavily on student feedback and peer observation as the primary technique for putting reflective practice into action. It leads to the notion that their comprehension of reflective practice is neither complete nor exhaustive. To improve their understanding of reflective practice, higher education can provide continuing assistance and direction to EFL teachers with mentorship programs, collaborative peer work, and training sessions in which experts in reflective practice guide them toward becoming reflective practitioners. Keywords: EFL, Professional Teachers, Reflective Practice, Teachers’ Comprehension